Modelling and analysis of an oscillatory dynamic system using the hybrid state approach: An experimental case - DOĞRUEL, MURAT (SAGE PUBLICATIONS LTD, 2006)
Many existing dynamic systems contain mechanical effects like inertia, elasticity and friction, as well as hysteretic effects, relays, flip-flops and discrete decision makers, sensors and actuators. The effective modelling of such systems is essential for a thorough analysis and to improve our understanding. In general, both discrete and continuous dynamics are simultaneously in action and interact with each other. In this work, a non-linear oscillatory dynamic system, which has both continuous and discrete dynamics, is considered, and an experimental setup is constructed. For an efficient and effective analysis, the discrete and continuous dynamics are treated simultaneously using a hybrid state modelling approach. The simulations and experiments are per-formed for different conditions of the system to investigate their effect on its behaviour. The use of the hybrid state modelling approach for dynamic systems containing interacting discrete and continuous state dynamics is demonstrated both numerically and experimentally.
Keywords: dynamic systems; discrete dynamics; continuous dynamics; hybrid systems; modelling